Strategic warfare in cyberspace - Rattray, Gregory J., 1962- (The MIT Press, 2001)
A comprehensive analysis of strategic information warfare waged via digital means as a distinct concern for the United States and its allies. In the "information age," information systems may serve as both weapons and targets. Although the media has paid a good deal of attention to information warfare, most treatments so far are overly broad and without analytical foundations. In this book Gregory Rattray offers a comprehensive analysis of strategic information warfare waged via digital means as a distinct concern for the United States and its allies. Rattray begins by analyzing salient features of information infrastructures and distinguishing strategic information warfare from other types of information-based competition, such as financial crime and economic espionage. He then establishes a conceptual framework for the successful conduct of strategic warfare in general, and of strategic information warfare in particular. Taking a historical perspective, he examines U.S. efforts to develop air bombardment capabilities in the period between World Wars I and II and compares them to U.S. efforts in the 1990s to develop the capability to conduct strategic information warfare. He concludes with recommendations for strengthening U.S. strategic information warfare defenses